Evaluation of Tourism Competitiveness of Ukraine's Regions - KOVALOV, Bohdan; BURLAKOVA, Iryna; VORONENKO, Viacheslav (Journal of Environmental Management and Tourism, 2017)
According to WEF, UNWTO, WTTC, World Travel & Tourism Market increased by 26,3% between 2010 through 2015 and now stands more than US$ 7,2 trillion (9,8% of global GDP). The number of international tourists increased by 75% and the number of persons employed in tourism around the world increased to 284 million. The objectives of this paper are: analysis of tourism competitiveness of Ukraine’s regions on the basis of relevant index calculation in 2013-2015; ranking of regions; analysis of the dynamics of changes in index and rankings by region; evaluation of tourism competitiveness level of regions. As results of research the set of indicators was formed to reflect the tourism competitiveness from a regional perspective. The Travel & Tourism Competitiveness Index (TTCI) for 24 regions and Kyiv city in 2013-2015 was calculated and rating was constructed. It was established that 88% of regions have a positive trend in the index changing and there are only 3 regions with a negative one. The ranking leaders are Kyiv city (1 st place), Lviv (2 nd place) and Chernivetska (3 rd place) regions. During 2013-2015, seven regions have worsened their positions in the overall rankings, losing from 1 to 9 positions; another nine regions on the contrary have risen in the rating by 1 to 9 positions; and other nine regions have saved their positions in ranking. It was established that 92−96% of regions have an intermediate level of tourism competitiveness in 2013-2015 and 4−8% of regions have an upper-intermediate. The results of the study show that tourist industry of Ukraine’s regions has an intermediate level of the development (68% of regions have TTCI > 3,5 in 2015). It is proved by WEF calculation according to which TTCI of Ukraine is 3,83.